Eukaryotic Ribosomal Protein S5 of the 40S Subunit: Structure and Function - Qiu, Lijuan; Chao, Wen; Zhong, Shan; Ren, An-Jing (International journal of molecular sciences, 2023)
The ribosomal protein RPS5 is one of the prime proteins to combine with RNA and belongs to the conserved ribosomal protein family. It plays a substantial role in the process of translation and also has some non-ribosome functions. Despite the enormous studies on the relationship between the structure and function of prokaryotic RPS7, the structure and molecular details of the mechanism of eukaryotic RPS5 remain largely unexplored. This article focuses on the structure of RPS5 and its role in cells and diseases, especially the binding to 18S rRNA. The role of RPS5 in translation initiation and its potential use as targets for liver disease and cancer are discussed.